Pengaruh Media Manik-Manik dalam Pembelajaran Penjumlahan dan Pengurangan Terhadap Hasil Belajar Siswa Kelas 1 SDN Ngrimbi 2 - Afifah, Laila Roidhotun; Rochmania, Desty Dwi (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Mathematics is a branch of knowledge that is essential for all people in the world to know. Because in daily life, one cannot escape from things related to numbers. Determining time is also included in the field of mathematics. Currency is also one of the topics included in mathematics learning materials. Researchers have the goal of determining the learning outcomes of addition and subtraction for first-grade students at Ngrimbi 2 Elementary School before and after using bead media. To determine if there is a difference in the influence of bead media on mathematics learning for first-grade students at Ngrimbi 2 Elementary School. Researchers designed the study using a quantitative method with a Pre-experimental design type of research called One Group Pretest-Posttest Design. By obtaining accurate data from students who have not received treatment and after receiving treatment. The results of this study in the pre-test showed that the average score of the group was 57.65. However, the group showed a different average after receiving treatment with an average group score of 76.4. Meanwhile, in the Kolmogorov-Smirnov test table, both pretest and posttest data show that the p-value > α = 0.05, indicating a normal distribution. In the Paired Samples t-test, there is a difference in the average between pretest and posttest of -5.784. Additionally, the significant value (2-tailed) is 0.000 < 0.005, indicating a significant difference between pretest and posttest results.